3 - ‘We no go sit down’: CAFA and the Struggle Against Structurally Adjusted Education in Africa - Alidou, Ousseina; Caffentzis, George; Federici, Silvia (Journal of Higher Education in Africa, 2008)
This paper is a short history of the Committee for Academic Freedom in Africa (CAFA) since its founding in 1991 to the present. It describes CAFA documenta- tion of the formation of an Africa-wide student movement against the structural adjustment of African universities. It also details some of CAFA’s campaigns in defence of student struggles against both the World Bank’s role in propagating the introduction of tuition fees and the cutting of housing and food subsidies to stu- dents and the repressive action of the African governments against protesting students. We argue that academic freedom also includes the right to be involved in the production of knowledge and hence to have access to the means of its produc- tion. To deny Africans such a right in this period in history is to condemn them to the fate of being the damned of the earth once more and to put the ability of Africans to manage their own resources in peril.